Mitophagy - the degradation of dysfunctional organelles - Vainshtein, Anna (Henry Stewart Talks, 2018)
Mitochondrial function and dysfunction, Mitochondrial quality control and degradation, Autophagy, Mitophagy, the mitochondria-specific autophagy pathway, Mechanisms and molecules involved in Mitophagy, Physiological and pathophysiological roles of Mitophagy